2018
DOI: 10.1063/1.5037062
|View full text |Cite
|
Sign up to set email alerts
|

An efficient water force field calibrated against intermolecular THz and Raman spectra

Abstract: A polarizable water model is presented which has been calibrated against experimental THz and Raman spectra of bulk water. These low-frequency spectra directly probe the dynamics, and thereby intermolecular interactions, on time scales relevant to molecular motions. The model is based on the TL4P force field developed recently by Tavan and co-workers [J. Phys. Chem. B 117, 9486 (2013)], which has been designed to be transferable between different environments; in particular, to correctly describe the electrost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 90 publications
2
45
0
Order By: Relevance
“…It has been shown that the intensity of that band is related to inter-molecular charge transfer upon hydrogen bonding. [58][59][60] On the other hand, the third prominent mode in the THz spectrum of water, the librational mode around 600 cm −1 , is essentially missing in the oxygen velocity autocorrelation function. It is missing since the rotation of a water molecule around its center-of-mass barely affects the position of the oxygen (the band is present in the hydrogen velocity autocorrelation function, 24 which is however not considered here).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the intensity of that band is related to inter-molecular charge transfer upon hydrogen bonding. [58][59][60] On the other hand, the third prominent mode in the THz spectrum of water, the librational mode around 600 cm −1 , is essentially missing in the oxygen velocity autocorrelation function. It is missing since the rotation of a water molecule around its center-of-mass barely affects the position of the oxygen (the band is present in the hydrogen velocity autocorrelation function, 24 which is however not considered here).…”
Section: Resultsmentioning
confidence: 99%
“…Charge transfer also takes place upon hydrogen bond formation and is believed to be responsible for water surface charging 8-10 and some peaks in the low-frequency IR [11][12][13][14][15][16][17][18][19] and Raman spectra. [20][21][22] Assigning fixed partial atomic charges to water has been a popular practice in modeling water in simulations, and these so-called non-polarizable water models, [23][24][25][26][27][28][29] often parameterized empirically, have shown great success in reproducing a wide range of experimental properties of water, 29 including its sophisticated phase diagram, while failing in scenarios that call for flexible partial atomic charges, such as the low-frequency region of the IR spectrum [30][31][32][33] and water in heterogeneous environments. [34][35][36][37] Charge models can be grouped into different categories with very different philosophies.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] On the other hand, the complex and largeamplitude motions occurring at terahertz frequencies have recently been related to a wide-variety of bulk phenomena, for example phase transformations, 11,12 mechanical responses, 5,13,14 electron-phonon coupling, 15,16 and gas-capture in porous mate-persurface to a level of accuracy that enables a proper determination of the weak forces responsible for terahertz dynamics. Over the past two decades there have been a number of advances that have dramatically improved the description of terahertz dynamics, 29 including the determination of IR intensities in periodic simulations, 30 the incorporation of dispersion forces, 31,32 more advanced basis sets, 33,34 force fields, 35 and density functionals, 36 and so on. But, by-far the most critical to accurate terahertz analyses has been the development of robust periodic boundary condition simulations.…”
Section: Introductionmentioning
confidence: 99%